Flat Broadband Chaos Generation Using a Semiconductor Laser Subject to Asymmetric Dual-Path Optical Feedback - Yang, Qiang; Qiao, Lijun; Wei, Xiaojing; Zhang, Boxin; Chai, Mengmeng; Zhang, Jianzhong; Zhang, Mingjiang (Journal of lightwave technology, 2021)
A method of generating flat broadband chaos by using a semiconductor laser subject to asymmetric dual-path optical feedback is proposed and demonstrated experimentally. In the asymmetric dual-path optical feedback, one path is connected with an optical band-pass filter (OBPF) to form filtered path, and the other is a traditional optical feedback path named non-filtered path. Through the beating frequency effect between the filtered mode and the non-filtered chaos mode, a chaotic signal with the standard bandwidth of 36.1 GHz and the spectrum flatness of 5.8 dB is generated experimentally. Furthermore, the effects of filter frequency detuning, filter bandwidth and feedback strength on the bandwidth and flatness of chaos are investigated. The results show that the bandwidth enhancement and the flat spectrum can be achieved simultaneously in a wide range of operating parameters.